Training for Hygienic Tofu Making at WKRI Paroki St. Ignatius Loyola Semplak, Bogor - Tati Barus; Yasinta Ratna Esti Wulandari; Rory Anthony Hutagalung; Dionysius Subali (MITRA: Jurnal Pemberdayaan Masyarakat, 2020)
Tofu is a traditional Indonesian food that has many advantages and is made with a very simple manufacturing process. However, knowledge about tofu and the process of making hygienic and healthy tofu is still low in Indonesia. Therefore, the present community service aims to improve public knowledge about tofu as a healthy food and how tofu is made. The community service activities were implemented to residents of the WKRI at Paroki St. Ignatius Loyola, Semplak, Bogor 16310, which consisted of counseling, demonstration, and mentoring methods. Monitoring was conducted to measure the level of success achieved by participants in producing healthy tofu. Participants' perceptions about tofu were evaluated through a survey method and improving knowledge was measured through tests (pretest and posttest). The results of counseling, demonstration, and mentoring succeeded in improving the participants' skills as evidenced by their success in making hygienic and healthy tofu. The survey results showed participants' improving knowledge about hygienic and healthy tofu and participants’ higher motivation to produce hygienic and healthy tofu independently. All participants appreciated the community service activities. They also appreciated the exceptional ability of the facilitator in delivering the materials.